2021
DOI: 10.3390/metabo11070429
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and Depression in Women: An 1H-NMR Metabolomic Study

Abstract: Fibromyalgia is a chronic and systemic syndrome characterized by muscle, bone, and joint pain. It is a gender-specific condition with a 9:1 incidence ratio between women and men. Fibromyalgia is frequently associated with psychic disorders affecting the cognitive and emotional spheres. In the reported work, we compared 31 female fibromyalgia patients to 31 female healthy controls. They were analyzed for biochemical clinical parameters, for autoimmune markers, and were subjected to 1H-NMR metabolomics analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…6,47 Significant metabolite combinations allowed prediction of disease susceptibility, 86 monitoring of disease course, 28 or response to treatment. 82 Moreover, metabolomics analysis have previously shown variations of metabolites in various biological fluids in patients with chronic painful disorders such as fibromyalgia, 15,26,36,59,61 musculoskeletal pain, 53,67,88,99 complex regional pain syndrome, 2,65 vestibulodynia, 49 and in orofacial pain such as temporomandibular disorder in women.…”
Section: Introductionmentioning
confidence: 99%
“…6,47 Significant metabolite combinations allowed prediction of disease susceptibility, 86 monitoring of disease course, 28 or response to treatment. 82 Moreover, metabolomics analysis have previously shown variations of metabolites in various biological fluids in patients with chronic painful disorders such as fibromyalgia, 15,26,36,59,61 musculoskeletal pain, 53,67,88,99 complex regional pain syndrome, 2,65 vestibulodynia, 49 and in orofacial pain such as temporomandibular disorder in women.…”
Section: Introductionmentioning
confidence: 99%
“…Together, our findings highlight the complex and multifactorial effects of fibromyalgia microbiota across several systems in mice. Similarly, humans with fibromyalgia exhibit a wide range of phenotypes, including the sensitization of the peripheral and central nervous systems 20,21 , immune dysregulation [22][23][24] , and metabolomic alterations 3,[25][26][27][28][29] . Notably, individuals with fibromyalgia often experience functional gastrointestinal disorders, including irritable bowel syndrome (IBS) and functional dyspepsia 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…This investigation was exclusively carried out with women, due to the significantly higher prevalence of fibromyalgia among women compared to men. Research has consistently shown that the majority of individuals seeking medical care for fibromyalgia are women [33][34][35], reporting a ratio of approximately 9:1 between women and men.…”
Section: Discussionmentioning
confidence: 99%